Relación De La Inteligencia Emocional Con La Eficacia Laboral De Los Conductores De Servinaltra (2023)
Emotional intelligence is of great importance in the workplace. This study seeks to determine the relationship between emotional intelligence and the work effectiveness of Servinaltra drivers. Therefore, the application of an emotional intelligence test and a review of the 360º performance evaluation were carried out.